HRV FEATURES IN THE ADAPTATION PROCESS OF ADOLESCENT FOOTBALL PLAYERS TO SYSTEMATIC PHYSICAL LOADS - A.A. Ruziyeva (Journal of modern medicine, 2026)
Currently, HRV holds a central place in sports medicine as an integral indicator of the state of autonomic regulation and adaptive reserves. Time-domain HRV parameters reflect overall variability and the contribution of the parasympathetic division, while frequency-domain HRV parameters characterize the balance of sympathetic and parasympathetic influences. Well-adapted athletes, including adolescents, have higher SDNN and RMSSD values and a relatively low LF/HF ratio, which is interpreted as a predominance of vagal control at rest. Objective. To study HRV values to assess cardiovascular adaptation to systematic physical loads in young football players. Materials and Methods. The study involved 50 adolescents aged 13–16 who regularly play football at the Football Academy of the Samarkand Region, and 20 of their peers who do not engage in regular sports. The characteristics of their HRV parameters were analyzed. Conclusion. Measuring HRV helps to manage the training process not approximately, but on a scientific basis, thereby preserving the health of players and reducing the number of injuries on the team. The presented data demonstrate the absence of sympathetic hyperactivation in adolescent athletes and the predominance of the parasympathetic division of the autonomic nervous system.